Role of ultrasonography in diagnosis of scrotal disorders: A review of 110 cases - S. Thinyu (2018)
Objective: To determine the role of ultrasonography in diagnosis of scrotal disorders. Materials and methods: This study was carried out after institutional review board approval was granted, and informed consent was waived. Between January 2005 and January 2007, 144 patients aged 12 years and older with scrotal symptoms, who underwent scrotal ultrasonography (US), were retrospectively reviewed. The clinical presentation, outcome, and US results were analysed. The presentation symptoms were divided into three groups including scrotal pain, painless scrotal mass or swelling, and others. Surgery was performed in 32 patients. Results: Of 144 patients, 110 had clinical follow-up and constituted the material of this study. The patients ranged in age from 13 to 82 years (mean 38.6 years). Of 110 patients, 84 (76.4%) presented with scrotal pain, 21 (19%) had painless scrotal mass or swelling and 5 (4.5%) had other symptoms. Of the 84 patients with scrotal pain, 52 had infection, 4 had testicular torsion, 7 had testicular trauma, 10 had varicocele, 4 had hydrocele, 1 had epididymal cyst, 1 had scrotal sac and groin metastases, and 5 had unremarkable results. Of the 21 patients who presented with painless scrotal mass or swelling, 18 had extratesticular lesions and 3 had intratesticular lesions. All the extratesticular lesions were benign. Of the 3 intratesticular lesions, one was due to tuberculous epididymo-orchitis, one was non-Hodgkin's lymphoma, and one was metastasis from liposarcoma. Of the 5 patients who presented with other symptoms, 4 had undescended testes, and 1 had gynaecomastia. US gave incorrect diagnosis in only one patient with scrotal pain. Conclusion: The most common cause of scrotal pain was infection. The most common cause of scrotal mass or swelling was extratesticular lesion. US plays an important role in the diagnosis of scrotal disorders and in planning for proper management. © 2009 Biomedical Imaging and Intervention Journal. All rights reserved.